Intellectual Property Rights Violations in Illegal Cigarettes in Indonesia from an Interlegality Perspective - Lutfiadi, Lutfiadi; Wardani , Win Yuli; Camelia, Noer Dini; Aprilia , Gabriel; Iskandar, Toillah (Hakamain: Journal of Sharia and Law Studies, 2025)
This study analyzes the philosophical, theoretical, constitutional, and international foundations underlying the inappropriateness of granting legal protection to trademarks attached to illegal products, particularly non-excise (illicit) cigarettes. From the perspectives of natural law, positivism, utilitarianism, and social-function theory, intellectual property rights (IPR) are recognized as legitimate rights but are always constrained by morality, public order, and social interests. Constitutional analysis shows that although the 1945 Constitution acknowledges IPR, Article 28J affirms limitations based on public interest and public order, rendering trademarks on illegal products ineligible for protection.National positive law, through the Trademark Law and the Excise Law, explicitly precludes the possibility of granting trademark protection to products that violate the law. Within the philosophical framework of Pancasila, protecting trademarks for illegal cigarettes contradicts the values of morality, humanity, national interest, democracy, and social justice. Meanwhile, international law—through TRIPS, the Paris Convention, and global health regimes such as the FCTC—provides explicit grounds for states to exclude IPR protection on the basis of morality, public order, and the protection of public health. Using a normative legal research method, this study concludes that trademark protection for illegal cigarettes cannot be justified conceptually or normatively. IPR is not absolute; it embodies a social function, and the state has an obligation to reject or revoke protection for trademarks that support unlawful practices in order to realize social justice and uphold the integrity of the national legal system.